RELATIONSHIP BETWEEN HUSBAND SUPPORT AND MOTHER'S INTEREST IN USING INDEPENDENT FP IN MALASAN WETAN VILLAGE - Widiarti, Wieke; Hanifah, Iis; Natalia, Mega Silvian (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
One of the goals listed in the 2020-2024 Strategic Plan (Renstra) is a peaceful, independent and happy family by strengthening the implementation of family planning independently. There are 2 methods of contraception, namely hormonal and non-hormonal either according to government programs (free) or independently (paid). The purpose of this study was to analyze the relationship between husband's support and mother's interest in using independent family planning in Malas Wetan Village. This study uses a correlational analysis design with a cross sectional approach. The sample data were all active independent family planning acceptors in Lalaman Wetan in January 2022 a total of 99 PUS who met the inclusion criteria using simple random sampling technique. Data collection includes, coding, editing, and tabulating which then the data is analyzed by computer with the Spearman test p value: 0.05. The results showed that respondents had husbands with a very supportive category of 50 respondents (50.5%), respondents using Mandiri Family Planning with a high interest category of 54 respondents (54.5%) and p value: 0.000. The conclusion of the study is that there is a relationship between husband's support and mother's interest in using independent family planning in Malasan Wetan Village (p = 0.000 <0.05). It is hoped that midwives, assisted puskesmas officers and other health workers can provide counseling or provide periodic and ongoing education to the public about Contraceptive Devices.